A Christology of religions - O'Collins, Gerald (Maryknoll, NY, Orbis Books, 2018)
In his latest book, Gerald O'Collins adopts the person and saving work of Christ as the master key for organizing themes commonly treated by theologies of religion. But he does so through the lens of Christology to examine important themes that these theologies typically ignore: the relevance of the theology of the cross for thinking about "the others"; the impact of Christ's priesthood on all men and women of all places and times; the efficacy of prayer for "the others" inspired by love; and the nature of faith available for these "others." This "Christology of religions," O'Collins argues, can help break the current stalemate widely affecting the theology of religions, and breathe new life into thinking about religious "others."
Incarnation as caring for "the others" and sharing the sufferings of all -- Christ's high-priestly intercession for all -- The universal presence of Christ and the Holy Spirit -- The church joins Christ in loving intercession for all people -- The faith of the suffering "others" -- Discerning the presence of Christ and the Spirit -- Dialogue and relations with Muslims and Jews.
Includes bibliographical references and indexes.
Keywords: Jesus Christ -- Person and offices; Christianity and other religions; Theology of religions (Christian theology)